Urban Transport and Hybrid Vehicles - Soylu, Seref (IntechOpen, 2010)
This book is the result of valuable contributions from many researchers who work on both technical and nontechnical sides of the field to be remedy for typical road transport problems. Many research results are merged together to make this book a guide for industry, academia and policy makers.